Kebijakan Pemilihan Umum Pasangan Calon Tunggal Presiden dan Wakil Presiden - Syah, Ardan Ardian (Journal of Governance and Administrative Reform, 2022)
Abstract This study focuses on the discussion related to the constitutionality of a single candidate pair in the election of President and Vice President. With the space given by the constitution and from the provisions of Law Number 7 of 2017 and also strengthened through the decision of the Constitutional Court, then the behavior of political parties themselves causes a single candidate in the election of President and Vice President to occur. The existence of a single candidate can be accepted by democracy when faced with an empty box which will create problems and negative views in the implementation of democracy in Indonesia. The existence of a single candidate in the presidential and vice presidential elections raises constitutionality problems so that the existence of a single candidate in the presidential election is highly avoided. This study uses a normative juridical method, with a statutory approach, and a conceptual approach. Abstrak Dalam Penelitian ini memfokuskan pembahasan terkait konstitusionalitas pasangan calon tunggal dalam pemilihan Presiden dan Wakil Presiden. Dengan adanya ruang yang diberikan konstitusi dan dari ketentuan Undang-Undang Nomor 7 tahun 2017 serta dikuatkan juga melalui putusan Mahkamah Konstitusi yang kemudian adanya perilaku partai politik itu sendiri menyebabkan calon tunggal dalam pemilihan Presiden dan Wakil Presiden dapat saja terjadi. Keberadaan calon tunggal dapat diterima oleh demokrasi apabila dihadapkan dengan kotak kosong yang mana akan memunculkan permasalahan dan pandangan yang negatif dalam pelaksanaan demokrasi di Indonesia. Keberadaan calon tunggal dalam pelaksanaan pemilihan Presiden dan Wakil Presiden memunculkan problem konstitusionalitas sehingga adanya calon tunggal dalam Pilpres sangat dihindarkan. Penelitian ini menggunakan metode yuridis normatif, dengan pendekatan perundang-undangan, dan pendekatan konseptual.